2004
DOI: 10.1097/01.ju.0000131601.06286.26
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of 3 Different Methods of Anesthesia Before Transrectal Prostate Biopsy: A Prospective Randomized Trial

Abstract: Any form of analgesia/anesthesia was superior to none. The combination of PNB plus gel provided significantly better analgesia compared to PNB alone or tramadol. If this can be duplicated in other trials, the combination may be accepted as the new gold standard of anesthesia for prostate biopsy. The efficacy of tramadol was similar to that of PNB, and was free of complications. Therefore, tramadol may have a role before prostate biopsy, which needs to be explored.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
61
1
4

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(72 citation statements)
references
References 18 publications
6
61
1
4
Order By: Relevance
“…Obek et al found that the combination of peri-prostatic block and intra-rectal lidocaine worked better then periprostatic block alone in a randomized study of 300 men. 60 This is supported by a study involving 223 men showing that peri-prostatic nerve block in addition to intra-rectal local anesthetic provided superior pain relief compared to peri-prostatic nerve block and intrarectal placebo. 61 Raber et al, noticed a similar benefit to combined peri-prostatic nerve block and intra-rectal local anesthetic over peri-prostatic nerve block alone especially with respect to pain during insertion of the ultrasound report.…”
Section: Combination Peri-prostatic Block and Intra-rectal Local Anessupporting
confidence: 50%
“…Obek et al found that the combination of peri-prostatic block and intra-rectal lidocaine worked better then periprostatic block alone in a randomized study of 300 men. 60 This is supported by a study involving 223 men showing that peri-prostatic nerve block in addition to intra-rectal local anesthetic provided superior pain relief compared to peri-prostatic nerve block and intrarectal placebo. 61 Raber et al, noticed a similar benefit to combined peri-prostatic nerve block and intra-rectal local anesthetic over peri-prostatic nerve block alone especially with respect to pain during insertion of the ultrasound report.…”
Section: Combination Peri-prostatic Block and Intra-rectal Local Anessupporting
confidence: 50%
“…Alternatively, the application of an intrarectal gel may make the procedure easier without such a high cost. Obek et al categorised patients into four groups including a control group, a periprostatic blockage group, a periprostatic blockage with intrarectal gel group, and a tradamol (codein analogue) group (13). They showed that the group in which analgesia and anaesthesia were provided undertook the procedure far better than the control group, which received no treatment for pain.…”
Section: Discussionmentioning
confidence: 99%
“…Vanni [55] No difference in hematuria and rectal bleeding between LA & CT. Nambirajan [44] No significant difference in hematuria (8.4% vs. 10.4%), rectal bleeding (8.4% vs. 6.3%), hematospermia (18.8% vs. 23%) and infection (8.3% vs. 10.4%) between groups (LA vs. CT). Obek [45] Higher rate of complications in periprostatic infiltration but not significantly different. Figure 9 Table showing studies that reported their rates of complications or adverse events from PPNB (LA) when compared to controls (CT).…”
Section: Intrarectal Lignocainementioning
confidence: 99%
“…[34][35][36]42,44,[51][52][53]19,56 They were not specified in the remaining 15 trials. 14,[37][38][39][40][41]43,[45][46][47][48][49][50]54,55 For the trials assessing the efficacy of PPNBs, two types of controls were used. Either no anesthesia at all was given or an equivalent volume of normal saline injection was administered.…”
Section: Study Description and Validitymentioning
confidence: 99%